Early mechanisms of neutrophil activation and transmigration in acute lung injury - Cagle, L. A.; Linderholm, A. L.; Franzi, L. M.; Last, J. A.; Simon, S. I.; Kenyon, N. J.; Harper, R. W. (Frontiers in Physiology, 2022)
Neutrophil transmigration is multifactorial and primarily driven by selectins and beta2-integrins (CD11b/CD18), whose expression are dependent on the underlying stimulus. Ventilator-induced lung injury (VILI) results in a predominantly CD18-independent mechanism of neutrophil recruitment, while direct endotoxin-induced lung injury results from a CD18-dependent mechanism. We previously observed that lack of NADPH oxidases DUOX1 and DUOX2 resulted in reduced neutrophil influx in a VILI model of lung injury but had no influence on neutrophil influx after LPS exposure. Based on these observations, we hypothesized that DUOX1/DUOX2 are an important component of CD18-independent mechanisms of neutrophil recruitment in the lung. We exposed Duoxa-/- (KO) mice and Duoxa+/+ (WT) mice to either an intratracheal exposure of lipopolysaccharide (LPS/endotoxin)-or high tidal volume ventilation and compared expression of neutrophil markers between groups. As previously observed, neutrophilic influx into the airways was significantly impaired in the Duoxa-/- (KO) mice after VILI, but not after LPS exposure. LPS-induced lung injury resulted in upregulation of CD11b+ neutrophils and shedding of CD62L and CD162 regardless of DUOX expression, whereas VILI resulted in upregulation of CD49+ neutrophils in the Duoxa+/+ (WT) mice but not the Duoxa-/- (KO) mice. These data suggest DUOX is required for CD18-independent mechanisms of neutrophil recruitment in the lung.